Effect of oral communication strategies training on the development of Malaysian English as a second language learners' strategic competence - Gan, Lai Kuen; Rafik-Galea, Shameem; Chan, Swee Heng (Australian International Academic Centre, 2017)
This study investigates the use of oral communication strategy instruction on English as a Second Language (ESL) learners’ oral communicative performance and their strategic competence. The treatment involved 12 weeks of training using oral communication strategies such as circumlocution, appeal for help, clarification request, fillers, comprehension check, confirmation checks, self-repair and topic avoidance. Strategies were integrated into the learners’ Communicative English 2 Course syllabus with Mechanical Engineering content. The study involved two intact control (n=34) and experimental groups (n=54). The control group only received the normal Communicative English course with no explicit focus on communication strategies (CS) while the experimental group received CS training designed with metacognitive strategies. Pre and post-test procedures were used to assess the effectiveness of the training and learners’ strategic competence. Five instruments were used to collect the data (oral proficiency test, oral communication test, transcripts of oral communication test, unstructured interview and self-report). The findings revealed that the experimental group significantly outperformed the control group after the training and the learners’ self-reports also revealed positive results. The results also revealed that the learners frequently used literal translation from their first language in their communication.